Age-Related Susceptibility to Muscle Damage Following Mechanotherapy in Rats Recovering From Disuse Atrophy. (28th June 2021) - Hettinger, Zachary R; Hamagata, Kyoko; Confides, Amy L; Lawrence, Marcus M; Miller, Benjamin F; Butterfield, Timothy A; Dupont-Versteegden, Esther E
Abstract: The inability to fully recover lost muscle mass following periods of disuse atrophy predisposes older adults to lost independence and poor quality of life. We have previously shown that mechanotherapy at a moderate load (4.5 N) enhances muscle mass recovery following atrophy in adult, but not older adult rats. We propose that elevated transverse stiffness in aged muscle inhibits the growth response to mechanotherapy and hypothesize that a higher load (7.6 N) will overcome this resistance to mechanical stimuli. F344/BN adult and older adult male rats underwent 14 days of hindlimb suspension, followed by 7 days of recovery with (RE + M) or without (RE) mechanotherapy at 7.6 N on gastrocnemius muscle. The 7.6 N load was determined by measuring transverse passive stiffness and linearly scaling up from 4.5 N. No differences in protein turnover or mean fiber cross-sectional area were observed between RE and RE + M for older adult rats or adult rats at 7.6 N. However, there was a higher number of small muscle fibers present in older adult, but not adult rats, which was explained by a 16-fold increase in the frequency of small fibers expressing embryonic myosin heavy chain. Elevated central nucleation, satellite cell abundance, and dystrophin − /laminin + fibers were present in older adult rats only following 7.6 N, while 4.5 N did not induce damage at either age. We conclude that age is an important variable when considering load used during mechanotherapy and age-related transverse stiffness may predispose older adults to damage during the recovery period following disuse atrophy.